Child’s risk profiles and levels of intervention with families in the Public System of Social Services. - Grimaldi-Puyana, Víctor; Garrido-Fernández, Miguel; Jiménez-Morago, Jesús (Anales de Psicología / Annals of Psychology, 2012)
The aim of this study is to know the risk profile related with child well-being of families in Social Services and to verify whether the families attended in the different levels of intervention show differential profiles of risk. In addition, the relationships of certain socio-demographic variables and indicators of risk with the child welfare were analyzed. For it, the professionals of the Andalusian Social Services were requested for applying the Child Well-being Scales to 770 families. The results show that the level of child well-being in these families tends to be low and that there exist very remarkable differences between profiles of risk that support the technical decisions adopted. Likewise, there is stated that socio-demographics variables as level of income, educational level, labour status and marital status of the parents, or that family risk variables present in parents as history of child abuse, psychological problems or aggressive behaviour were also related with the child well-being.